PERAWATAN ARMADA BUS TERHADAP KELANCARAN OPERASI PADA PERUSAHAAN ANGKUTAN DARAT - Irwan Chaerudin; Patriot Oskar; Yulianti Keke (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The objective of this research is to find out the effect of bus fleet maintenance towards the operational stability in PT. Primajasa. Data collection methods applied in this research were field research and library study. Data were analyzed by using simple regression analysis techniques, coefficient correlation analysis, coefficient determinant, and hypothesis testing. The result of the research shows that the linier regression equation Y = 5.603 + 0.880 X. In every increase of bus fleet maintenance, it is followed by an increase in operation stability in 0.880 in constants of 5.603. The correlation coefficient of bus fleet maintenance towards the operation stability is positive and strong in 0.710. The correlation of bus fleet maintenance towards the operation stability is strong and positive since it is affected by operational stability of 50.4% while the 49.6% are affected by other factors.